Robotic-assisted sleeve gastrectomy with simultaneous Roux-en-Y cystojejunostomy in a patient with sever obesity and a pancreatic pseudocyst: a case report - Zhang, Zheng; Wang, Lun; Wei, Zhiqiang; E, Changyong; Jiang, Tao (Frontiers in Surgery, 2024)
We tried to apply a new surgical method to treat obesity combined with pancreatic pseudocyst and achieved satisfactory results.We report a case of a severely obese patient with pancreatic pseudocyst who underwent robotic-assisted sleeve gastrectomy, while the pseudocyst was incised and cyst-jejunostomy was performed. The operation was successful, and the patient was discharged on the 8th day after the procedure. There were no complications during the perioperative period. After 12 months of follow-up examinations, the patient's pancreatic pseudocyst disappeared. Additionally, there was a significant decrease in body weight, body mass index, and other indicators. As a result, obesity and related metabolic diseases were completely relieved. Conclusions: This case summarizes and presents the experience of using robotic bariatric surgery for the treatment of pancreatic pseudocyst. This case report indicates that this surgical procedure is both safe and effective for patients with pancreatic pseudocyst who also have obesity and related metabolic diseases.